2005
DOI: 10.1038/sj.gt.3302556
|View full text |Cite
|
Sign up to set email alerts
|

The systemic administration of Ig-4-1BB ligand in combination with IL-12 gene transfer eradicates hepatic colon carcinoma

Abstract: We have previously shown that the local-membrane bound 4-1BB ligand and IL-12 gene transfer induced a significant antitumor response in a mouse colon carcinoma model. However, a high viral dose was required in order to achieve the best efficacy. In this study, we hypothesize that the systemic administration of soluble Ig-4-1BB ligand can give rise to better T-cell immune activation than local gene delivery. With potential clinical applications in mind, we further compare whether the natural 4-1BB ligand fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Consistent with this hypothesis, murine tumor cells engineered to express 4-1BBL exhibited enhanced immunogenicity (16), and adoptive transfer of T cells expressing 4-1BBL resulted in potent tumor rejection (17,18). Systemic administration of agonistic anti-4-1BB monoclonal antibodies enhanced tumor immunity and tumor rejection in a murine melanoma tumor model (19,20). Finally, we have previously shown that an oncolytic vaccinia virus expressing 4-1BBL had significant antitumor activity in a carcinoembryonic antigen transgenic murine carcinoma model.…”
Section: Introductionsupporting
confidence: 51%
“…Consistent with this hypothesis, murine tumor cells engineered to express 4-1BBL exhibited enhanced immunogenicity (16), and adoptive transfer of T cells expressing 4-1BBL resulted in potent tumor rejection (17,18). Systemic administration of agonistic anti-4-1BB monoclonal antibodies enhanced tumor immunity and tumor rejection in a murine melanoma tumor model (19,20). Finally, we have previously shown that an oncolytic vaccinia virus expressing 4-1BBL had significant antitumor activity in a carcinoembryonic antigen transgenic murine carcinoma model.…”
Section: Introductionsupporting
confidence: 51%
“…Anti-4-1BB has been also used in combination with IL-12-expressing dendritic cell (24), human telomerase reverse transcriptase gene therapy (25), dendritic cell-based vaccine (4), IL-12 gene therapy (3), and radiation (26). Soluble 4-1BB ligand in combination with IL-12 gene therapy produced potent antitumor response against hepatic colon carcinoma model (27). Induction of potent antitumor effect by the use of single-chain Fv of anti-4-1BB is another important approach (28,29).…”
Section: Cd11cmentioning
confidence: 99%
“…Consistent with this, synergistic effects of IL-12 with 4-1BB on antitumor CD8 ϩ T-cell responses have been recognized by others in mouse models. 43,44 TGF-␤1 ubiquitously exists in the body. We found that effects of IL-4 on generation of NKG2D Ϫ 4-1BB Ϫ CD8 ϩ T cells became more apparent in the presence of TGF-␤1.…”
Section: Discussionmentioning
confidence: 99%